STRENGTHENING THE NATION VIA- NATIONAL LANGUAGE MAINTENANCE AND SOCIAL IDENTITY REINFORCEMENT - Dedi Aprianto (Universitas Pendidikan Mandalika, 2016)
Conveniently, human language could be taken into consideration as a worth property at outset belonged to the whole man. It has been comprising a proper way for conveying thoughts, expression, and aims as well. A particular language is not only regarded as a national one but as a personal identity of nation. Thus, a language might articulate a given identity belonging to society such as way of speech and way of thinking. The presence of different way of talking is resulted by the different social background. Moreover, it is regarded as part of the groups existing in a community having sameness in terms of synchronic participation to produce a common language. In relevance to language as marvelous identity in which set of each human ought to be maintained through Education, language Policies, and language improvement. A nation might be considered as being progressive while possessing a particular language representing a typical and fervent identity. Having had fervent idealized identity, a nation could have been led to flourishing one in terms of expancement through a national language as well as ethnic language maintenance. In line with social changes passing in capacious social aspects which trigger towards human language as social, economy, politic, and culture. These social aspects of life could have been affected by unawareness of national language maintenance. Thus, the writer puts forward social change in terms of language shift to language death. A national language is considered as a identity symbolizing the existence of it, signifying the unite of folk, and triggering towards progressive traits of nation. In case of indigenous language lies on paramount role in terms of national aims due to the fact that aboriginal language belonging to societies can signifies its identity as well as represents the culture. A common type of language ideology are standard language ideologies, the belief that language homogeneity is beneficial to society to construct interconnection in the hope that they may properly make language live. Thus, the expancement of national language as well as indigenous language would be increasingly wide-spread towards national Advancement.